2016
DOI: 10.1136/openhrt-2016-000535
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microvascular obstruction on semiautomated techniques for quantifying acute and chronic myocardial infarction by cardiovascular magnetic resonance

Abstract: AimsThe four most promising semiautomated techniques (5-SD, 6-SD, Otsu and the full width half maximum (FWHM)) were compared in paired acute and follow-up cardiovascular magnetic resonance (CMR), taking into account the impact of microvascular obstruction (MVO) and using automated extracellular volume fraction (ECV) maps for reference. Furthermore, their performances on the acute scan were compared against manual myocardial infarct (MI) size to predict adverse left ventricular (LV) remodelling (≥20% increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…6 However, acute MI size is influenced by a number of factors including the timing of the CMR scan, the dose of contrast used, the time elapsed following contrast administration and acquisition of late gadolinium enhancement imaging and the method used for the quantification of MI size. 6, 91 Therefore, there is an urgent need for the CMR community to come up with a consensus position to standardize the acquisition of late gadolinium enhancement imaging and the quantification of MI size in future studies. 6 This would no doubt help to strengthen the robustness of this technique and would also facilitate prospective or retrospective collaborative research with merging of CMR data from different centers around the world.…”
Section: Future Directionsmentioning
confidence: 99%
“…6 However, acute MI size is influenced by a number of factors including the timing of the CMR scan, the dose of contrast used, the time elapsed following contrast administration and acquisition of late gadolinium enhancement imaging and the method used for the quantification of MI size. 6, 91 Therefore, there is an urgent need for the CMR community to come up with a consensus position to standardize the acquisition of late gadolinium enhancement imaging and the quantification of MI size in future studies. 6 This would no doubt help to strengthen the robustness of this technique and would also facilitate prospective or retrospective collaborative research with merging of CMR data from different centers around the world.…”
Section: Future Directionsmentioning
confidence: 99%
“…Some studies showed that 5-SD was promising 39, 40, 41, but others showed that it overestimated MI size 42, 43. The n-SD technique requires the remote myocardium to be appropriately nulled and free of artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The Otsu technique does not require a region of interest as a reference and has been shown to accurately delineate MI size (40). But 2 subsequent studies showed that Otsu overestimated MI size 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…The authors could have considered using the reference standard of manual delineation of AAR and MI size by experienced operators, rather than semiautomated thresholding methods, which are known to have their limitations. 5,6 The presence of microvascular obstruction (MVO) on the acute CMR scan is known to pseudonormalize the ECV, 5,7 because of failure of the gadolinium chelate to penetrate areas of MVO, which could have affected MI size regression, thereby making it challenging to estimate chronic MI size from the acute ECV in patients with MVO. Finally, the study used ≤75% transmural MI on the follow-up CMR scan to define viable myocardium, instead of the conventionally accepted definitions of ≤50% for viability on CMR.…”
Section: See Article By Garg Et Almentioning
confidence: 99%
“…5,11 The regression in MI size represents the gradual resolution of myocardial edema, intramyocardial hemorrhage and MVO, and the gradual replacement of necrotic tissue with fibrosis in the chronic infarct. 11 Furthermore, LV remodeling leads to thinning of the infarcted territory and compensatory LV hypertrophy of the adjacent and remote myocardium, resulting in the overall reduction in LGE mass observed in the chronic phase.…”
Section: Can Acute Ecv Maps Be Used To Accurately Delineate the Chronmentioning
confidence: 99%